Efforts to Improve Volleyball Under Passing Using Modified Balls - Aril Pratama (Gladi : Jurnal Ilmu Keolahragaan, 2025)
This study aims to improve students’ ability in performing the underhand passing technique in volleyball through the application of modified ball learning media. The research employed classroom action research (CAR) following the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects of the study were 20 students from class X at Umbulsari Senior High School, Jember. Data were collected through tests and observations on students’ underhand passing skills during the learning process. The results showed that in the first cycle, 13 students (65%) achieved the minimum mastery criteria (KKM = 70), while in the second cycle, the number increased to 17 students (85%). This indicates that using modified balls as a learning medium can significantly improve students’ volleyball underhand passing skills. The use of varied and engaging learning designs enhances students’ motivation, participation, and skill acquisition in physical education, particularly in volleyball basic techniques.